COX2 Enhances Neovascularization of Inflammatory Tenocytes Through the HIF-1α/VEGFA/PDGFB Pathway - Deng, Bin; Xu, Pu; Zhang, Bingyu; Luo, Qing; Song, Guanbin (Frontiers in Cell and Developmental Biology, 2021)
Tendon injuries are among the most challenging in orthopedics. During the early tendon repair, new blood vessel formation is necessary. However, excessive angiogenesis also exacerbates scar formation, leading to pain and dysfunction. A significantly worse outcome was associated with higher expression levels of hypoxia-inducible factor-1 alpha (HIF-1α), and its transcriptional targets vascular endothelial growth factor A (VEGFA) and platelet-derived growth factor B (PDGFB), but the underlying molecular mechanisms remain unclear. In this study, lipopolysaccharide (LPS) was used to induce an inflammatory response in tenocytes. LPS increased the tenocytes inflammatory factor COX2 expression and activated HIF-1α/VEGFA/PDGFB pathway. Moreover, the conditioned medium from the tenocytes boosted rat aortic vascular endothelial cells (RAOECs) angiogenesis. Furthermore, Trichostatin A (TSA), an inhibitor of histone deacetylase, was used to treat inflammatory tenocytes. The expression levels of HIF-1α and its transcriptional targets VEGFA and PDGFB decreased, resulting in RAOECs angiogenesis inhibition. Finally, the dual-luciferase reporter gene assay and chromatin immunoprecipitation (ChIP) assay proved that the HIF-1α/PDGFB pathway played a more critical role in tenocytes angiogenesis than HIF-1α/VEGFA pathway. TSA could alleviate angiogenesis mainly through epigenetic regulation of HIF-1α/PDGFB pathway. Taken together, TSA might be a promising anti-angiogenesis drug for abnormal angiogenesis which is induced by tendon injuries.